(untitled) (Washington, 1999)
This report is one of three volumes about the economy of Ukraine that was produced during 1998 - 1999 by an innovative, experimental partnership of World Bank and Ukrainian experts. Traditionally the World Bank's periodic economic studies on borrowing member countries, studies known as "Country Economic Memorandums," are written almost entirely by staff and consultants from the Bank's main office based on a 2 - 3 week visit to the country. The report is written in Washington, formally reviewed inside the Bank, further revised, and then, as much as 6 - 9 months later, it is sent to the Government for review and clearance.
Keywords: Economic policy,Economic conditions; 1991-,1991-; Ukraine,Ukraine